Malice - Jackson, Lisa (New York Zebra Books, 2009)
The scent is unmistakable: the perfume that his beautiful first wife, Jennifer, always wore. Opening his eyes in the hospital room, New Orleans detective Rick Bentz sees her standing in the doorway. But Jennifer died twelve years ago. Once out of the hospital, Bentz begins to see Jennifer everywhere, haunting and taunting him, then vanishing without a trace. Could she still be alive? But it was Bentz who identified her body after the horrible car wreck. He's never doubted it until now. When a copy of Jennifer's death certificate arrives emblazoned with a red question mark, Bentz follows the postmark trail to Los Angeles, straight into a killer's web. Each new discovery only serves as a chilling reminder of how little he really knew about his first wife. Then the murders begin, each victim a part of Jennifer's past, each grisly corpse pointing to Bentz as the prime suspect. A diabolical killer has been waiting patiently, silently. Soon it will be Bentz's turn to suffer for his sins. But he won't be the only one: now his new wife is the killer's prime target.